Microscopic observations on microtomed surface of ice - Hyakutake, Kinji; Moribe, Atsushi; Miyamoto, Atsushi; Shimohara, Kimiko; Shoji, Hitoshi (2002)
P(論文) Surface hollows appearing after microtome shaving were observed on poly-and single crystal specimens under an optical microscope in a cold room laboratory. Characteristic shell-shaped hollows appeared with their major axis perpendicular to the shaving direction. Fewer hollows appeared at specimen surfaces when the basal plane of the ice crystal was parallel or perpendicular to the specimen surface. The results observed could be easily interpreted if cleavage cracks form parallel or perpendicular to the basal plane near the blade edge during the microtome shaving process. departmental bulletin paper